STUDI KASUS : PERAWATAN LUKA ABSES MENGGUNAKAN MODERN DRESSING HYDROFIBER DAN EPITEL CREAM DI PRAKTIK MANDIRI GRIYA AFIAT KOTA MAKASSAR - Salmah; Wa Ode Sri Asnaniar; Nur wahyuni Munir; Nur Ilah Padila (Jurnal Kesehatan, 2026)
Background: An abscess is a skin infection caused by the accumulation of pus, commonly due to Staphylococcus aureus. This condition is more frequently found in patients with diabetes mellitus due to impaired immunity and microcirculation, which slows the wound-healing process. Conventional wound care is often insufficient in controlling exudate and preventing infection, thus requiring modern dressings such as Hydrofiber silver, which effectively absorbs exudate and provides antimicrobial activity to support healing. Objective: This study aims to evaluate the effectiveness of Hydrofiber silver and zinc epithelial cream in the management of abscess wounds. The intervention focused on exudate control, infection prevention, periwound protection, and acceleration of granulation and epithelialization processes in patients treated at the Griya Afiat Independent Practice, Makassar City. Method: A case study was conducted on Mr. AH, a 61-year-old male with an abscess wound on the back. Wound assessment and treatment were carried out during two visits, on Monday and Thursday. The procedure included wound cleansing, application of Hydrofiber silver as the primary dressing, and zinc epithelial cream on the periwound area to maintain moisture and prevent irritation. Results: Over two visits, initial improvements were observed. Wound size decreased from 1.3 × 1.6 cm to 1.2 × 1.4 cm. The wound showed subcutaneous depth, a tunnel < 2 cm, 25% slough, 50% granulation tissue, 25% epithelialization, moderate purulent exudate, and surrounding skin with hypopigmentation, mild edema, and induration < 2 cm. The total score was 29, with an estimated healing time of 5–6 weeks. Conclusion: The combination of Hydrofiber silver and zinc epithelial cream effectively contributed to exudate control and periwound protection, although continued care is needed to optimize the healing of abscess wounds.